Snowmelt Infiltration and Macropore Flow in Frozen Soils: Overview, Knowledge Gaps, and a Conceptual Framework. Issue 1 (8th November 2018) - Mohammed, Aaron A.; Kurylyk, Barret L.; Cey, Edwin E.; Hayashi, Masaki
Abstract : Core Ideas: Review highlights the hydrological importance of macropore flow in frozen soils. Governing flow mechanisms and infiltration and refreezing dynamics are discussed. Research is needed to integrate macropore flow and soil freeze–thaw theory. Dual‐domain models of macropore flow should be adapted to frozen ground. A conceptual framework for modeling frozen macroporous soils is proposed. Macropore flow in frozen soils plays a critical role in partitioning snowmelt at the land surface and modulating snowmelt‐driven hydrological processes. Previous descriptions of macropore flow processes in frozen soil do not explicitly represent the physics of water and heat transfer between macropores and the soil matrix, and there is a need to adapt recent conceptual and numerical models of unfrozen macropore flow to account for frozen ground. Macropores remain air filled under partially saturated conditions, allowing preferential flow and meltwater infiltration prior to ground thaw. Nonequilibrium gravity‐driven flow can rapidly transport snowmelt to depths below the frost zone or, alternatively, infiltrated water may refreeze in macropores and restrict preferential flow. As with unfrozen soils, models of water movement in frozen soil that rely solely on diffuse flow concepts cannot adequately represent unsaturated macropore hydraulics. Dual‐domain descriptions of unsaturated flow that explicitly define macropore hydraulic characteristics have been successful under unfrozen conditions but need refinement for frozen soils. In particular, because pore connectivity and hydraulic conductivity are influenced by ice content, modeling schemes specifying macropore–matrix interactions and refreezing of infiltrating water are critical. This review discusses the need for research on the interacting effects of macropore flow and soil freeze–thaw and the integration of these concepts into a framework of coupled heat and water transfer. As a result, it proposes a conceptual model of unsaturated flow in frozen macroporous soils that assumes two interacting domains (macropore and matrix) with distinct water and heat transfer regimes.